School Climate and Academic Hardiness on Students’ Subjective Well-Being in Boarding School with Student Engagement as Mediator - Na’imah, Tri; Sriyanto, Sriyanto; Nur'aeni, Nur'aeni; Azzahra, Nabilla Feylisha (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Students in boarding schools face additional pressures due to dual curriculum, high cognitive load, personal problems such as family homesickness, feelings of not belonging, and poor sleep patterns that compound worsening student well-being. This study examines the relationship between school climate and academic hardiness with student subjective well-being, with the mediation of student engagement among students in boarding schools. Data were collected using the Student Subjective Wellbeing Questionnaire (SSWQ; CR=0.941), School Climate Scale (SCR; CR=0.895), The Academic Hardiness Scale (AHS; CR=0.921), and Student Engagement Scale (SES; CR=0.902). A total of 519 junior and senior high school students who participated in Islamic boarding school programs in Banyumas Regency, Central Java, Indonesia, were involved in the study. The data were analysed using AMOS (Analysis of Moment Structures) software to conduct structural model analysis and hypothesis validation, to evaluate the relationship between variables. The results indicated that student engagement mediates school climate and student subjective well-being. Student engagement also mediates the relationship between academic hardiness and student subjective well-being. Students in boarding schools suggested to have a positive perception of the school environment and academic hardiness in facing academic problems and challenges to achieve well-being while living in the dormitory.